Kesiapan Wanita Usia 45-55 Tahun dalam Menghadapi Perubahan Masa Menopause - Putri Andanawarih; Ni’matul Ulya (Jurnal Kebidanan Harapan Ibu Pekalongan, 2021)
Menopause is a process of transition from the productive period to the nonproductive period due to the reduction in the hormones estrogen and progesterone. The average age of most women going through menopause is between the ages of 45 and 55. Some women consider menopause to be a frightening thing, this worry comes from the thought that they will become unhealthy so that they feel anxious. In Indonesia, by 2025 it is estimated that there will be 60 million menopausal women. Readiness to face menopause is a condition for mothers to prepare themselves for menopause both physically, mentally and psychologically. The purpose of this study was to determine the readiness of women aged 45-55 years in facing menopause changes in Kuripan Yosorejo Village. This research is a quantitative study with a cross sectional study design and using the chi square statistical test. The results obtained p value 0.01 <α (0.05), which means that there is a relationship between knowledge of menopause and readiness to face changes in menopause. With this research, it is hoped that menopausal mothers can increase their knowledge about reproductive health, especially about menopause by reading many books about menopause or through other information media so that it can increase understanding of how to deal with menopause and reduce complaints before menopause, especially for menopausal mothers at a level lack of knowledge.